Efficiency or Equity? Determinants of Regional Allocation of Infrastructure Investment in the Republic of Korea - Lee, Jongyearn (The Korean Economic Review, 2022)
We used a structural model to determine which aspects of efficiency and equity criteria were advocated in allocating investment in transportation infrastructure by region in the Republic of Korea during the period of 2001–2014. The estimation by the generalized method of moments indicated that the country’s regional allocation of public investment favored equity enhancement rather than efficiency gain. Empirical findings also include evidence of the substitutionary relationship between the investments by the central and regional governments, as well as the excess capital stock of transportation infrastructure compared with the optimum. The infrastructure needs and regional financial conditions had limited effects on the past allocation of investment. Political influence was exerted with respect to electoral productivity rather than partisanship.